Co-prevalence of arterial aneurysm location - a correlation analysis based on a retrospective cross-sectional observational study - Körfer, Daniel; Kilian, Samuel; Grond-Ginsbach, Caspar; Hatzl, Johannes; Hakimi, Maani; Böckler, Dittmar; Erhart, Philipp (Vasa, 2024)
Background: The aim of this retrospective single-centre cross-sectional observational study was to investigate co-prevalence of arterial aneurysm location systematically. Patients and methods: Patients with the diagnosis of any arterial aneurysm from January 2006 to January 2016 were investigated in a single centre. Patients with hereditary disorders of connective tissue, systemic inflammatory disease, or arterial pathologies other than true aneurysms were excluded. Aneurysm locations were assessed for every patient included. For patients with at least two co-existing aneurysms, co-prevalence of aneurysm location was investigated by calculating correlation coefficients and applying Fisher’s exact test. This study report is prepared according to the STROBE statement. Results: Of 3107 identified patients with arterial aneurysms, 918 were excluded. Of the remaining 2189 patients, 951 patients with at least two aneurysms were included in the study. Bilateral aneurysm combinations of paired iliac, femoral and popliteal arteries showed the highest correlation (ϕ=0.35 to 0.67), followed by bilateral combinations of subclavian (ϕ=0.36) and internal carotid (ϕ=0.38) arteries. Abdominal aortic aneurysms in combination with visceral artery aneurysms (ϕ=−0.24 to −0.12), popliteal arteries (ϕ=−0.22) and the ascending aorta (ϕ=−0.19) showed the lowest correlation, followed by the descending aorta in combination with the common iliac arteries (ϕ=−0.12 to −0.13). Conclusions: In our study sample, aneurysm co-prevalence was highly non-random. This should be considered in the context of aneurysm screening programs.